Mantacaprella macaronensis, a new genus and species of Caprellidae (Crustacea: Amphipoda) from Canary Islands and Cape Verde - Vázquez-Luis, Maite; Guerra-García, José M.; Carvalho, Susana; Png-Gonzalez, Lydia (Zootaxa, 2013)
Mantacaprella macaronensis new genus, new species, is described based on specimens collected from Canary Islands and Cape Verde. Mantacaprella is close to the genera Pariambus, Pseudolirius, Propodalirius and Paracaprella, but can be distinguished by the combination of the following characteristics: pereopods 3, 4 and 5 two-articulate; pereopods 6 and 7 six-articulate; mandibular molar present and palp absent; male abdomen with a pair of well-developed appendages. The new species has been found living in Cymodocea nodosa meadows and Caulerpa prolifera beds from 8.8 to 14.6 m depth in Gran Canaria (Canary Islands), and in natural rocky and artificial habitats (shipwrecks) at 25 m in Sal Island (Cape Verde). Even though the new species is one of the dominant amphipods inhabiting meadows of Cymodocea nodosa in Gran Canaria and in Cape Verde, it had not been described so far. This reflects the lack of knowledge on Macaronesian invertebrates, such as amphipods, and the need of further taxonomical studies to better characterise the whole biodiversity of this region and to design adequate programmes of management and conservation.